2019
DOI: 10.1371/journal.pone.0219626
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania DNA detection and species characterization within phlebotomines (Diptera: Psychodidae) from a peridomicile-forest gradient in an Amazonian/Guianan bordering area

Abstract: In the border region between Brazil and French Guiana, American cutaneous leishmaniasis is a worrisome public health issue, and entomological studies are required there to better identify classical and putative emerging transmission patterns. The present study aimed to detect and characterize Leishmania DNA in the phlebotomine population of Oiapoque (Amapá State, Brazil). Phlebotomines were captured in anthropized and wild environments in the outskirts of Oiapoque municipality, using CDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…This is similar to the results of some studies in Old World settings that found frequencies of between 0.3% to 7.0% in females that had both fed and not fed [ 44 , 45 ]. Our result is in concordance with the findings of several previous studies of vectors in different areas of Brazil where CL is endemic, which described Leishmania frequencies of between 3.4% and 8.1% [ 42 , 46 48 ]. In concordance with Souza-Ferreira et al .…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to the results of some studies in Old World settings that found frequencies of between 0.3% to 7.0% in females that had both fed and not fed [ 44 , 45 ]. Our result is in concordance with the findings of several previous studies of vectors in different areas of Brazil where CL is endemic, which described Leishmania frequencies of between 3.4% and 8.1% [ 42 , 46 48 ]. In concordance with Souza-Ferreira et al .…”
Section: Discussionsupporting
confidence: 93%
“…braziliensis [62][63][64] and their capacity to support infections with this parasite have been confirmed by Alexandre et al [65]. The genus Evandromyia presented the highest number of species and although there are no proven vector species within this genus, natural infection or Leishmania DNA has been detected in some species [66,67]. In studies conducted in Minas Gerais, Carvalho et al [68] detected Le.…”
Section: Plos Onementioning
confidence: 87%
“…Kent et al (30) Fouque et al (29) Vasconcelos dos Santos et al (31) Th. brachipyga In an ACL endemic area of Rio Branco, Acre State, where Th.…”
Section: (V) Braziliensismentioning
confidence: 99%
“…; one sample allowed characterisation at species level, with sequence compatible with L. (V.) braziliensis. (31) Trichophoromyia brachipyga Mangabeira, 1942 and/or Th. adelsonsouzai Vasconcelos dos Santos, Silva, Barata, Andrade & Galati, 2013 -In the Belo Monte hydroelectric system affected area in Pará State, Brazil, a program monitoring ACL transmission has been implemented since 2012, providing substantial knowledge on ecology and taxonomy of phlebotomines.…”
Section: (V) Braziliensismentioning
confidence: 99%
See 1 more Smart Citation